1983
DOI: 10.1080/00071668308416747
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary intake and of dietary concentration of copper sulphate on the laying domestic fowl: Effects on laying performance and tissue mineral contents

Abstract: Sixty white hybrid (Shaver 288) laying hens were subjected to three main dietary regimens for 5 d: ad libitum feeding of control and CuSO4-supplemented diets, force-feeding these same diets to the same intake as that of the ad libitum control diet and pair-feeding the control CuSO4-free diet to intakes equivalent to those of supplemented diets. Final body weight of the force-fed birds was significantly greater than of the other groups. Egg number and weight were significantly reduced as food intake decreased. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…When liver weights were expressed as a percentage of body weight, values indicated that 600 mg Cu/kg had an adverse effect compared with the control. The same phenomenon has been observed in laying hens by Pearce et al (1983) and Stevenson et al (1983).…”
Section: Resultssupporting
confidence: 83%
“…When liver weights were expressed as a percentage of body weight, values indicated that 600 mg Cu/kg had an adverse effect compared with the control. The same phenomenon has been observed in laying hens by Pearce et al (1983) and Stevenson et al (1983).…”
Section: Resultssupporting
confidence: 83%
“…Other workers Stevenson et al, 1983) indicated that high dietary concentrations of Cu fed to laying hens resulted in decreased liver weights. This reduction in liver weight was attributed to reduced feed intake, since force-fed birds showed an increase in liver weights.…”
Section: Discussionmentioning
confidence: 98%
“…Very high dietary levels of copper (Stevenson et al 1983; Richards 1997) in laying birds will cause a rapid cessation of egg production, whereas feeding laying hens a copper-deficient diet results in a shell membrane with a significantly reduced copper concentration and an abnormal structure (Baumgartner et al 1978; Richards 1997). …”
Section: Discussionmentioning
confidence: 99%